2016
DOI: 10.48550/arxiv.1612.08159
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The $Z_c(3900)$ peak does not come from the "triangle singularity"

Abstract: We compare contributions from the triangle diagram and the D D * bubble chain to the processes of e + e − → J/ψπ + π − and e + e − → (D D * ) ∓ π ± . By fitting the J/ψπ maximum spectrum and the D D * spectrum, we find that the triangle diagram cannot explain the new experimental results from BESIII Collaboration at center of mass at 4.23GeV and 4.26GeV, simultaneously. On the contrary, the molecular assignment of Zc(3900) gives a much better description.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…They concluded that it is not possible to distinguish between these scenarios at that time, which contradicted the conclusion of Ref. [804].…”
Section: The Z C Statesmentioning
confidence: 89%
See 1 more Smart Citation
“…They concluded that it is not possible to distinguish between these scenarios at that time, which contradicted the conclusion of Ref. [804].…”
Section: The Z C Statesmentioning
confidence: 89%
“…In Ref. [804], the same group noted that the triangle singularity mechanism did not produce the observed Z c (3900) peak. Their study again favors the molecular assignment for the Z c (3900).…”
Section: The Z C Statesmentioning
confidence: 96%
“…However, it is shown in Refs. [334,336] for the case of the Z c (3900) that the triangle singularity alone cannot accommodate the data available at various energies.…”
Section: Threshold Effects Without New Statesmentioning
confidence: 99%
“…In Refs. [1,26,37,44,67,78], it was demonstrated that the D 1 (2420) DD * triangle diagram is important for the understanding of the Z c (3900) . It can produce a resonance-like structure, which enhances the production of near-threshold resonances [11].…”
Section: B Production Amplitudesmentioning
confidence: 99%